2017
DOI: 10.1101/gad.294082.116
|View full text |Cite
|
Sign up to set email alerts
|

The telomeric DNA damage response occurs in the absence of chromatin decompaction

Abstract: Telomeres are specialized nucleoprotein structures that protect chromosome ends from DNA damage response (DDR) and DNA rearrangements. The telomeric shelterin protein TRF2 suppresses the DDR, and this function has been attributed to its abilities to trigger t-loop formation or prevent massive decompaction and loss of density of telomeric chromatin. Here, we applied stochastic optical reconstruction microscopy (STORM) to measure the sizes and shapes of functional human telomeres of different lengths and dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 39 publications
8
38
1
Order By: Relevance
“…Some generalities emerged from these analyses. As expected, most telomeres appeared spherical, but heterogeneous shapes were also observed 45 . Fig.…”
Section: Trf1hp1α Increases Irregularly-shaped Telomere Structuressupporting
confidence: 79%
“…Some generalities emerged from these analyses. As expected, most telomeres appeared spherical, but heterogeneous shapes were also observed 45 . Fig.…”
Section: Trf1hp1α Increases Irregularly-shaped Telomere Structuressupporting
confidence: 79%
“…The next day cell suspensions were dropped onto slides to prepare metaphase spreads, incubated 1min at 70°C in a wet chamber and dried for 16-24 h before FISH. FISH staining of human telomeric DNA was performed as described (Vancevska et al, 2017). Slides were rehydrated in 1× PBS for 5 min, treated with 4% formaldehyde in PBS for 5 min, washed 3x with 1xPBS and dehydrated with increasing amounts of ethanol (70%, 95%, 100%).…”
Section: Telomeric Pna-fish On Metaphase Spreadsmentioning
confidence: 99%
“…Indirect immunofluorescence detection of human ATM pS981, 53BP1 and γH2AX followed by telomeric FISH staining was performed as described (Vancevska et al 2017). For detection of ATM pS1981 before crosslinking, cells were fractionated with an ice-cold preextraction buffer containing 0.5% Triton X-100, 20mM HEPES-OH pH 7.5, 50mM NaCl, 3mM MgCl2 and 300mM sucrose for 7min.…”
Section: Indirect Immunofluorescence and Telomeric Fish (If-fish)mentioning
confidence: 99%
“…These massive telomere-clustering events are specific for ALT cancer cells and mostly contain APBs (ALT-associated promyelocytic leukemia [PML] bodies), damaged DNA, and DNA repair machinery. Moreover, these are also increased in response to double-strand breaks or stalled replication forks at telomeres (11,(40)(41)(42)(43)(44)(45)(46)(47)(48). It has also been previously reported that large telomeric foci contain extrachromosomal telomeric DNAs (49).…”
mentioning
confidence: 91%